Exploring the Role of Blended ELTeach Training and Institutional Support in Promoting the Professional Confidence of Indonesian Non-Native English-Speaking Teachers - Syahid, Abdul; Lie, Anita; Chau, Meng Huat (Register Journal, 2026)
In recent years, there has been a growing focus on the development of language teachers; however, how to effectively support and enhance their confidence remains largely under-researched and inadequately understood. This mixed-methods sequential explanatory study explores how a four-month blended teacher training program, combined with varying levels of institutional support, may enhance English teachers' confidence in language use and understanding essential teaching methodologies. The training program integrated the ELTeach platform, a globally recognized online training resource, with in-person workshops. The study involved 250 Indonesian teachers from Islamic elementary and secondary schools; however, it primarily reports on the findings from 26 participants, divided into two equal groups based on their perceived institutional support. Participants self-assessed their confidence levels before and after training. Results from mixed ANOVA analyses indicate that ELTeach-based training significantly increased ELT professional confidence; however, perceived institutional support and the combination of training with support did not yield a significant impact. Interviews with six participants—involving three teachers before and after training and three principals after the training—showed the impact of personal factors and the dynamics within the training program. The alignment between the quantitative and qualitative findings underscored the training potential to promote teacher professional confidence, regardless of the level of institutional support. The study concludes with the implications for the development of teacher professional development, especially in promoting teacher confidence.